РОЗРОБКА ТА ПЕРЕВІРКА АДЕКВАТНОСТІ МАТЕМАТИЧНОЇ МОДЕЛІ ТЕПЛОВОГО БАЛАНСУ РЕАКТОРУ З ЕЛЕКТРОТЕРМІЧНИМ ПСЕВДОЗРІДЖЕНИМ ШАРОМ - Simeiko, K.V. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
Supply of heat through combustion of organic fuel is impossible or economically unviable for the raw of high temperature processes due to it’s technological peculiarities. Some of these processes can be carried out in electrothermal fluidized bed reactors. Development of appropriate mathematical model for heat balance will allow prognostication of capacity needed to carry out specific process and improvement of electrothermal fluidized bed reactor. During the development of mathematical model methods of heat-mass exchange theory were applied.  Verification of appropriateness for mathematical model was carried out through comparison of experimental results and calculated values of the amount of heat needed to perform the process of methane pyrolysis in electrothermal fluidized bed and coefficient of thermal efficiency of electrothermal fluidized bed reactor. Comparison with real thermochemical process in electrothermal fluidized bed reactor confirms the appropriateness of mathematical model. Average deviation of mathematical model of heat balance and coefficient of thermal efficiency from obtained experimental values is 5…7 % and 6…9 % respectively. Proposed mathematical model can be applied in design of electrothermal fluidized bed reactors.